A preclinical study on cell therapy as an adjunct to surgical decompression in degenerative cervical myelopathy via accelerating blood spinal cord barrier reconstitution and neurological recovery - Hyun Woo Kim; Liang Yu Shi; Min Goo Lee; Ra Hye Kim; Zhi Yi Fan; Paul Aarne Koljonen; Graham Ka Hon Shea (Stem Cell Research & Therapy)
Abstract Background Degenerative cervical myelopathy (DCM) is the most common disorder affecting the cervical spinal cord in the developed world. Whilst surgery is effective, many patients suffer from residual neurological deficits post-decompression. Cell-based therapies have been studied for traumatic spinal cord injury models but not DCM and may be efficacious as an adjunct to surgical decompression via trophic factor secretion, parenchymal engraftment and/or blood spinal cord barrier reconstitution. Methods 98 SD rats at age 10–12 weeks underwent five weeks of cervical compression by inserting a water-absorbent polyurethane polymer at the C4 epidural space or received sham surgery. Decompression surgery was performed by removing the polymer. Treatment groups received BM-MSCs (bone marrow-derived marrow stromal cells) or BM-neurospheres intravenously or intracisternally at the time of decompression. Locomotor function (BBB testing, rotarod testing, Forelimb Score, and Hind Limb Score) and blood -spinal cord barrier (BSCB) recovery via Evans blue extravasation was observed in 35 rats during the 10-week post-decompression recovery period. 30 rats were used to determine in vivo cell distribution and comparative efficacy of intravenous (IV) or intracisternal (CIS) injection. The remaining rats were sacrificed to assess for the engraftment of transplanted cells. In vivo bioluminescent imaging (BLI) of EGFP-Luciferase BM-MSCs localized cells grossly to organ systems, whilst immunohistochemistry (IHC) of spinal cord specimens targeting anti-human antigens facilitated localization at the site of compression. Results BSCB disruption indicated by Evans Blue dye extravasation peaked at Week-4 post-decompression (DW4) and correlated with endoglin expression. Locomotor recovery after polymer removal was delayed with minor improvements observed by Week-8 post-decompression (DW8). IV and CIS injection of BM-MSCs did not lead to significant improvement in locomotor function (p = 0.101, Rotarod Test: PBS vs. CIS) nor of BSCB reconstitution by Day 10 post-decompression. BLI showed significant peripheral organ entrapment of IV BM-MSCs, while CIS BM-MSCs remained in the cervical region, with IHC demonstrating localization to the pia mater. At Day 20, both CIS BM-MSCs and BM-neurospheres similarly failed to significantly improve locomotor function (p = 0.136, Rotarod Test: PBS vs. BM-neurospheres) and transplanted cells were absent from the cervical cord parenchyma. Conclusion Human BM-MSCs and BM-neurospheres demonstrate limited efficacy as adjunct therapy to cervical decompression under the present experimental conditions. Adjusting insertable polymer hardness, cell number, and timing of cell transplantation may be future means to demonstrate potential therapeutic effectiveness.